STAFF. Housing lectures and projects in developing Argentina during the mid-sixties. - Longoni, Lucas (Universidad ORT Uruguay, 2018)
In the mid-sixties, the problem of access to housing in Argentina was channeled through various state initiatives, favoring the grouping of autonomous professionals as well as the concentration of professional studios linked to construction companies. The new conditions diversified the responses of the professional to the orders received from the State. In this context, the emergence of the STAFF studio (Goldemberg, Bielus and Wainstein Krasuk), which will be the most prolific of the period in terms of social housing, positioned, from its adherence to urban sociology, the theoretical discourse of social practices and motivational aspects of the addressees as a matrix of project design, relegating urban design to the last level. However, an approach to STAFF’s work reveals formal patterns that invariably replicate, contradicting their discursive propositions.